(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2007)
Objective: To observe the congenital abnormalities of female genital tract those are found in our population and their clinical implication. Place of study: Faridpur Medical College Hospital, Faridpur. Study period: January 2001 to December 2005. Methods and Materials: During the study period all cases of congenital abnormalities of female genital tract diagnosed in Faridpur Medical College Hospital were studied. Results: Total 74 women with different types of congenital abnormalities were detected. Though some cases were diagnosed incidentally, the various symptoms they produced were primary amenorrhea, apareunia, dyspareunia, hematocolpos and hematometra, infertility, prolapse uterus, abortions, ectopic pregnancy, premature labour and malpresentations. Among the 74 patients 35(47.3%) patients were treated at this centre, 24(32.4%) patients needed no treatment, 3(4%) patients were referred to higher centres for specialized treatment. Conclusion: Different types of congenital abnormalities of female genital tract are found in our population which cause various symptoms and complications. Though not all abnormalities need treatment and some need very simple treatment, there are some cases which need specialized treatment and expertise. (J Bangladesh Coll Phys Surg 2007; 25 : 23-28)